Multisine approximation of multivariate orthogonal random processes - Figwer, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
An approach to the synthesis and simulation of wide-sense stationary multivariate orthogonal random processes defined by their power spectral density matrices is presented. The approach is based on approximating the non-parametric power spectral density representation by the periodogram matrix of a multivariate orthogonal multisine random time-series.
Keywords: simulation random processes; multivariate orthogonal random processes; simulated identification; multisine random time-series; fast Fourier transform